Understanding health education needs of pregnant women in China during public health emergencies: a qualitative study amidst the COVID-19 pandemic - Xiaojuan Su; Yuezhen Zhang; Meide Chen; Xiangyang Xu; Guihua Liu (Frontiers Media S.A., 2024)
BackgroundPublic health emergencies impose unique challenges on pregnant women, affecting their physiological, psychological, and social wellbeing. This study, focusing on the context of the corona virus disease in 2019 (COVID-19) pandemic in China, aims to comprehensively explore the experiences of pregnant women amidst diverse public health crises. Herein, we investigate the health education needs of pregnant Chinese women in regard to public health emergencies to provide a scientific foundation for the development of targeted health education strategies.ObjectiveThe study described in this article aims to explore the health education needs of pregnant Chinese women in the context of public health emergencies specifying the types of emergencies of pandemics and to provide a scientific basis for targeted health education interventions.MethodsThirteen pregnant women were purposively selected, and the rationale for this sample size lies in the qualitative nature of the study, seeking in-depth insights rather than generalizability. Data collection involved semi-structured interviews, and the Colaizzi, which is a structured qualitative technique used to extract, interpret, and organize significant statements from participant descriptions into themes, providing a comprehensive understanding of their lived experiences.ResultsThe analysis yielded six prominent themes encompassing the following areas: I. Personal protection and vaccine safety; II. Knowledge of maternal health; III. Knowledge of fetal health; IV. Knowledge of childbirth; V. Knowledge of postpartum recovery; and VI. Knowledge sources of health education for pregnant women and their expectations of healthcare providers. Theme I was analyzed with two sub-themes (needs for personal protection knowledge, vaccine safety knowledge needs); Theme II was analyzed with three sub-themes (nutrition and diet, exercise and rest, sexual life); Theme III was analyzed with three sub-themes (medications and hazardous substances, pregnancy check-ups, and fetal movement monitoring); Theme IV was analyzed with three sub-themes (family accompaniment, analgesia in childbirth, and choice of mode of delivery); Theme V was analyzed with one sub-theme (knowledge of postnatal recovery); Theme VI was analyzed with one sub-theme (expectations of Healthcare providers). Sub-themes within each main theme were identified, offering a nuanced understanding of the multifaceted challenges faced by pregnant women during public health emergencies. The interrelation between sub-themes and main themes contributes to a holistic portrayal of their experiences.ConclusionThe study emphasizes the need for healthcare professionals to tailor health education for pregnant women during emergencies, highlighting the role of the Internet in improving information dissemination. It recommends actionable strategies for effective health communication, ensuring these women receive comprehensive support through digital platforms for better health outcomes during public health crises.